The Relative Advantages of Complaint Services Through the Pas Mantap Application (Pasuruan Aman dan Kondusif) - Zubaidah, Siti; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2020)
Based on instructions from the Ministry of State Apparatus Empowerment and Bureaucratic Reform (KemenPAN RB) it has implemented a policy that since 2014 is the year of public service innovation. With the increasing demands given by the community regarding excellent public services, innovation is needed to support these demands. Its tangible form, with the launch of the PAS MANTAP application as an application based on public complaint services. The purpose of this study is to determine, describe and analyze the relative advantages of complaint services through the MANTAP PAS application. This research uses descriptive qualitative method. The results in this study are relative advantages shown by the speed of response to each incoming report. Based on the authors' findings regarding the relative advantage that in terms of time, it can cut more time (time efficiency) and in one door that is passed on each report.